Preparation and application of cement / activated carbon composite material supercapacitor electrode
By using cement/activated carbon composites to prepare supercapacitor electrodes, the problems of pore activation and modification difficulties in existing electrode materials in applications are solved, and the effect of reducing production costs and improving electrochemical performance is achieved.
Patent Information
- Application Number
- CN202510044329.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-11
- Publication Date
- 2025-04-15
AI Technical Summary
Existing supercapacitor electrode materials such as activated carbon and carbon black have difficulties in pore activation and modification in practical applications, which limits their electrochemical properties in supercapacitors and the possibility of large-scale manufacturing.
Cement/activated carbon composite material is used as the supercapacitor electrode, and electrode sheets with good conductivity and structural pores are prepared by stirring cement and conductive activated carbon in deionized water, and then ultrasonic vibration and spraying are performed.
This method can significantly reduce production costs, improve production efficiency, and control the electrode sheet structure by regulating the amount of conductive activated carbon and the number of gold sprays, thereby studying its electrochemical performance and mechanism.
Smart Images

Figure CN119822735A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of supercapacitors, and in particular to the preparation of a cement / activated carbon composite material supercapacitor electrode and its application in supercapacitors. Background Art
[0002] At present, research on material technology of power resource storage system has become a feasible method to solve energy problems. With the energy crisis and carbon emission restrictions, research on new energy storage equipment - supercapacitor materials has once again become the focus. Supercapacitors are composed of three parts: electrodes, electrolytes, and diaphragms. The main determinant affecting the electrochemical performance of supercapacitors is the electrode material. As a type of supercapacitor, double-layer supercapacitors are composed of two electrodes fully soaked in electrolytes, separated by a diaphragm. When an external electric field is applied within a certain range (lower than the solution decomposition voltage), the anions and cations in the electrolyte migrate to the positive and negative electrodes respectively. Due to the electrostatic effect between the electrode and the electrolyte, the remaining positive and negative charges are close to each other, forming a double layer at the interface where the electrode and the electrolyte contact; the main electrode materials are carbon aerogel, graphene, carbon black, etc. Due to the advantages of electrochemical stability, fast charging and discharging, and low maintenance costs, double-layer supercapacitors are widely used in electric vehicles, energy storage systems, smart networks and other fields.
[0003] At present, due to the disadvantages of activated carbon, carbon black, etc., such as the need for activation, pore formation, and modification, their practical application in supercapacitors is greatly limited. As common materials, cement and activated carbon have attracted much attention in the application of supercapacitors. Although cement has been used as an electrolyte carrier diaphragm in supercapacitors, and there has been some research on mixing special carbon black with ordinary silicate cement to prepare new supercapacitor electrodes, it is still unclear whether cement can be made into a usable supercapacitor after doping it with other conductive materials (such as conductive activated carbon with a lower cost), its electrochemical properties, and whether it can be manufactured and produced on a large scale. Further research is needed. Summary of the invention
[0004] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.
[0005] In order to achieve these purposes and other advantages according to the present invention, a method for preparing a cement / activated carbon composite supercapacitor electrode is provided, comprising the following steps:
[0006] Step 1: adding cement and conductive activated carbon into deionized water and stirring to obtain a carbon-doped cement mixture;
[0007] Step 2: Add the carbon-doped cement mixture into the flexible silicone mold, smooth the upper and lower cross sections while compacting, and perform ultrasonic vibration;
[0008] Step 3: After ultrasonic vibration, place the block in a standard cement curing box for curing, and then demould it; demould it to obtain a carbon-doped cement block, and continue to cure it in a standard cement curing box to obtain a carbon-doped cement specimen;
[0009] Step 4: Place the carbon-doped cement specimen in a gold spraying instrument and spray it to obtain a carbon-doped cement electrode sheet.
[0010] Preferably, the cement is PO425 cement, the mass of the conductive activated carbon is 10-20% of the mass of the cement; and the mass percentage of the deionized water to the cement is 50-70%.
[0011] Preferably, in the step 1, the stirring time is 5 to 25 minutes, and the stirring speed is 200 to 600 rpm.
[0012] Preferably, in the step 2, the power of the ultrasonic vibration is 80 to 150 W, the frequency is 35 to 65 kHz, and the time of the ultrasonic vibration is 10 to 30 minutes.
[0013] Preferably, in step three, the temperature of the cement during curing in the standard curing box is 18-25° C. and the humidity is 90-96%.
[0014] Preferably, in step 4, each surface of the carbon-blended cement specimen is sprayed 5 to 20 times.
[0015] Preferably, the conductive activated carbon is pretreated, and the process is: adding the conductive activated carbon to the Ti4N3TxMXene treatment solution, heating to 60-70°C, and ultrasonically treating for 60-120 minutes; separating and drying to obtain the pretreated conductive activated carbon.
[0016] Preferably, the components of the Ti4N3Tx MXene treatment solution include, by weight: 8 to 15 parts of Ti4N3TxMXene compound, 3 to 8 parts of tryptophan, 40 to 70 parts of water, and 6 to 10 parts of n-hexanol.
[0017] Preferably, the ultrasonic power of the ultrasonic treatment is 300-500W, and the ultrasonic frequency is 35-65kHz.
[0018] The present invention also provides an application of a cement / activated carbon composite material supercapacitor electrode prepared by the preparation method described above in a supercapacitor.
[0019] The present invention has at least the following beneficial effects:
[0020] The present invention utilizes large-volume, low-priced cement and conductive activated carbon, and can prepare cement-based activated carbon electrode sheets according to the production of ordinary cement concrete and related requirements in GB / T 50081-2019 "Test Method for Mechanical Properties of Ordinary Concrete". Compared with traditional electrode sheets, this preparation technology can greatly reduce production costs and improve production efficiency; it can also change the amount of conductive activated carbon added and control the number of gold spraying, thereby realizing the regulation of the structure of the cement-based activated carbon electrode sheet, and then achieving the purpose of studying its electrochemical properties and its mechanism.
[0021] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a scanning electron microscope (SEM)-energy dispersive spectrum (EDX) image of the carbon-doped cement electrode sheet prepared in Example 1;
[0023] Figure 2 The cyclic voltammetry (CV) curve of the carbon-doped cement electrode sheet prepared in Example 1;
[0024] Figure 3 The charge and discharge curve of the carbon-doped cement electrode sheet prepared in Example 1;
[0025] Figure 4 This is the Nyquist plot of the AC impedance test of the carbon-doped cement electrode sheet prepared in Example 1. DETAILED DESCRIPTION
[0026] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.
[0027] It should be understood that terms such as “having”, “including” and “comprising” used herein do not specify the existence or addition of one or more other elements or combinations thereof.
[0028] In the present invention, the calculation formula of specific capacitance is:
[0029]
[0030] Where I(A) is the current, t(s) is the discharge time, A(cm 2 ) is the area of the cross section through which the current passes, and V(V) is the total voltage window.
[0031] Embodiment 1:
[0032] A method for preparing a cement / activated carbon composite material supercapacitor electrode comprises the following steps:
[0033] Step 1: According to the water-cement ratio of C30 cement concrete of 0.6, weigh 7.24g of PO425 cement and 1.0136g of conductive activated carbon (YP-80F supercapacitor / superelectric activated carbon, Japanese Kuraray Kurary water-based organic activated carbon), place them in a 50mL round-bottom flask, add 4.344g of deionized water, and stir at room temperature to form a carbon-doped cement mixed solution;
[0034] Step 2: placing the carbon-doped cement mixed solution on a magnetic stirrer and stirring at 400 rpm for 10 min until the cement and the activated carbon are fully mixed to obtain a carbon-doped cement mixture;
[0035] Step 3: Fill the stirred carbon-doped cement mixture into a 10*10*5 (mm) rectangular flexible silicone mold, vibrate it manually during the filling process, and smooth it after filling; then put the filled mold into a CNC ultrasonic oscillator and vibrate it according to the set parameters (power of 100 W, frequency of 40 kHz, time of 30 minutes);
[0036] Step 4: After the vibration is completed, put it into the curing box for short-term curing for 24 hours at a temperature of 20°C and a humidity of 90%;
[0037] Step 5: After the curing time is over, demoulding is performed and the specimen is placed in a curing box again for curing for 28 days at a temperature of 20°C and a humidity of 90%. After the curing time is over, demoulding is performed to obtain a carbon-doped cement specimen;
[0038] Step 6: Place the carbon-doped cement specimen in a gold spraying instrument and spray it 10 times according to the specified spraying times, each time for 30 seconds, with a thickness of less than 20 nm to obtain a carbon-doped cement electrode sheet.
[0039] Figure 1 This is a SEM-EDX image of the internal cross section of the carbon-doped cement electrode sheet prepared in Example 1. It can be seen from the figure that the electrode sheet is mainly composed of C, Si and O elements, the C element is evenly distributed, and the interior of the electrode sheet is rich in pores.
[0040] Figure 2 This is the CV curve of the carbon-doped cement electrode sheet prepared in Example 1. It can be seen that under the electrochemical test conditions of 20mV / s, 100mV / s and 500mV / s, the cyclic voltammetry curve of the electrode is a symmetrical curve that is approximately rectangular, which indicates that the prepared carbon-doped electrode has good cycle reversibility and capacitance characteristics.
[0041] Figure 3 This is the charge and discharge curve of the carbon-doped cement electrode sheet prepared in Example 1. It can be seen that the electrode can be charged and discharged normally under the working current of 10mA, 20mA and 50mA; and the GCD image shows that the electrode has a certain capacitance.
[0042] The specific capacitance calculation formula shows that the specific capacitance is 10 mA cm -2 When C s =0.058F / cm 2 , at 50mAcm -2 When Cs = 0.055F / cm 2 .
[0043] Figure 4 To implement the Nyquist plot of the AC impedance test of the carbon-doped cement electrode sheet prepared in 1, the test frequency range is set to 0.01Hz-10000Hz. It can be seen that the curve is composed of an arc-like curve and a straight line, proving that its electrochemical performance consists of two processes: electron transfer occurs in the high-frequency region, and ion diffusion occurs in the low-frequency region; the starting point does not start from (0,0), which is due to the internal resistance of the electrolyte in the three-electrode system.
[0044] Embodiment 2:
[0045] A method for preparing a cement / activated carbon composite material supercapacitor electrode comprises the following steps:
[0046] Step 1: Add 5 g of conductive activated carbon (YP-80F supercapacitor / superelectric activated carbon, Japanese Kuraray Kurary water-based organic activated carbon) to 20 g of Ti4N3Tx MXene treatment solution (10 g of Ti4N3Tx MXene compound, 5 g of tryptophan, 60 g of water, and 8 g of n-hexanol), heat to 60°C, and ultrasonically treat for 90 min (ultrasonic power of 500 W, ultrasonic frequency of 45 kHz); separate and dry to obtain pretreated conductive activated carbon;
[0047] According to the 0.6 water-cement ratio of C30 cement concrete, 7.24 g of PO425 cement and 1.0136 g of pretreated conductive activated carbon were weighed and placed in a 50 mL round-bottom flask, 4.344 g of deionized water was added, and stirred at room temperature to form a carbon-cement mixed solution;
[0048] Step 2: placing the carbon-doped cement mixed solution on a magnetic stirrer and stirring at 400 rpm for 10 min until the cement and the activated carbon are fully mixed to obtain a carbon-doped cement mixture;
[0049] Step 3: Fill the stirred carbon-doped cement mixture into a 10*10*5 (mm) rectangular flexible silicone mold, vibrate it manually during the filling process, and smooth it after filling; then put the filled mold into a CNC ultrasonic oscillator and vibrate it according to the set parameters (power of 100 W, frequency of 40 kHz, time of 30 minutes);
[0050] Step 4: After the vibration is completed, put it into the curing box for short-term curing for 24 hours at a temperature of 20°C and a humidity of 90%;
[0051] Step 5: After the curing time is over, demoulding is performed and the specimen is placed in a curing box again for curing for 28 days at a temperature of 20°C and a humidity of 90%. After the curing time is over, demoulding is performed to obtain a carbon-doped cement specimen;
[0052] Step 6: Place the carbon-doped cement specimen in a gold spraying instrument, spray 10 times according to the specified spraying times, each time for 30 seconds, with a thickness of less than 20 nm, to obtain a carbon-doped cement electrode sheet;
[0053] The specific capacitance calculation formula shows that the carbon-doped cement electrode sheet of this embodiment has a specific capacitance of 10 mA cm -2 When C s =0.061F / cm 2 From the content of this embodiment, it can be seen that pre-treating the conductive activated carbon with the Ti4N3Tx MXene treatment solution and loading MXene on the conductive activated carbon can significantly improve the specific capacitance of the carbon-doped cement electrode sheet.
[0054] Embodiment 3:
[0055] A method for preparing a cement / activated carbon composite material supercapacitor electrode comprises the following steps:
[0056] Step 1, add 5g of conductive activated carbon (YP-80F supercapacitor / superelectric activated carbon, Japanese Kuraray Kurary water-based organic activated carbon) to 20g of Ti4N3Tx MXene treatment solution (10g of Ti4N3Tx MXene compound, 5g of tryptophan, 60g of water, and 8g of n-hexanol), heat to 60°C, and ultrasonically treat for 90min (ultrasonic power of 500W, ultrasonic frequency of 45kHz); separate and dry to obtain a solid product; add the solid product to a supercritical reaction device, and soak it in a supercritical acetone-water system at a temperature of 365°C and a pressure of 20MPa for 15min; separate and dry to obtain pretreated conductive activated carbon; the volume ratio of acetone to water in the supercritical acetone-water system is 3:1;
[0057] According to the 0.6 water-cement ratio of C30 cement concrete, 7.24 g of PO425 cement and 1.0136 g of pretreated conductive activated carbon were weighed and placed in a 50 mL round-bottom flask, 4.344 g of deionized water was added, and stirred at room temperature to form a carbon-cement mixed solution;
[0058] Step 2: placing the carbon-doped cement mixed solution on a magnetic stirrer and stirring at 400 rpm for 10 min until the cement and the activated carbon are fully mixed to obtain a carbon-doped cement mixture;
[0059] Step 3: Fill the stirred carbon-doped cement mixture into a 10*10*5 (mm) rectangular flexible silicone mold, vibrate it manually during the filling process, and smooth it after filling; then put the filled mold into a CNC ultrasonic oscillator and vibrate it according to the set parameters (power of 100 W, frequency of 40 kHz, time of 30 minutes);
[0060] Step 4: After the vibration is completed, put it into the curing box for short-term curing for 24 hours at a temperature of 20°C and a humidity of 90%;
[0061] Step 5: After the curing time is over, demoulding is performed and the specimen is placed in a curing box again for curing for 28 days at a temperature of 20°C and a humidity of 90%. After the curing time is over, demoulding is performed to obtain a carbon-doped cement specimen;
[0062] Step 6: Place the carbon-doped cement specimen in a gold spraying instrument, spray 10 times according to the specified spraying times, each time for 30 seconds, with a thickness of less than 20 nm, to obtain a carbon-doped cement electrode sheet;
[0063] The specific capacitance calculation formula shows that the carbon-doped cement electrode sheet of this embodiment has a specific capacitance of 10 mA cm -2 When C s =0.065F / cm 2 .
[0064] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A method for preparing a cement / activated carbon composite supercapacitor electrode, characterized in that: The following steps are involved: Step 1: adding cement and conductive activated carbon into deionized water and stirring to obtain a carbon-doped cement mixture; Step 2: Add the carbon-doped cement mixture into the flexible silicone mold, smooth the upper and lower cross sections while compacting, and perform ultrasonic vibration; Step 3: After ultrasonic vibration, place the block in a standard cement curing box for curing, and then demould it; demould it to obtain a carbon-doped cement block, and continue to cure it in a standard cement curing box to obtain a carbon-doped cement specimen; Step 4: Place the carbon-doped cement specimen in a gold spraying instrument and spray it to obtain a carbon-doped cement electrode sheet.
2. The method for preparing a cement / activated carbon composite material supercapacitor electrode according to claim 1, characterized in that: The cement is PO425 cement, the mass of the conductive activated carbon is 10-20% of the mass of the cement; the mass percentage of the deionized water used is 50-70% of the mass of the cement used.
3. The method for preparing the cement / activated carbon composite material supercapacitor electrode according to claim 1, characterized in that: In the step 1, the stirring time is 5 to 25 minutes, and the stirring speed is 200 to 600 rpm.
4. The method for preparing a cement / activated carbon composite material supercapacitor electrode according to claim 1, characterized in that: In the step 2, the power of the ultrasonic vibration is 80 to 150 W, the frequency is 35 to 65 kHz, and the time of the ultrasonic vibration is 10 to 30 minutes.
5. The method for preparing the cement / activated carbon composite material supercapacitor electrode according to claim 1, characterized in that: In the step 3, the temperature of the cement in the standard curing box is 18-25° C. and the humidity is 90-96%.
6. The method for preparing a cement / activated carbon composite material supercapacitor electrode according to claim 1, characterized in that: In the step 4, each surface of the carbon-blended cement specimen is sprayed 5 to 20 times.
7. The method for preparing a cement / activated carbon composite material supercapacitor electrode according to claim 1, characterized in that: The conductive activated carbon is pretreated, and the process is as follows: adding the conductive activated carbon to a Ti4N3Tx MXene treatment solution, heating to 60-70° C., and ultrasonically treating for 60-120 minutes; separating and drying to obtain the pretreated conductive activated carbon.
8. The method for preparing the cement / activated carbon composite material supercapacitor electrode according to claim 7, characterized in that: The components of the Ti4N3Tx MXene treatment solution include, by weight: 8 to 15 parts of Ti4N3Tx MXene compound, 3 to 8 parts of tryptophan, 40 to 70 parts of water, and 6 to 10 parts of n-hexanol.
9. The method for preparing a cement / activated carbon composite material supercapacitor electrode according to claim 7, characterized in that: The ultrasonic power of the ultrasonic treatment is 300-500W, and the ultrasonic frequency is 35-65kHz.
10. Use of a cement / activated carbon composite material supercapacitor electrode prepared by the preparation method according to any one of claims 1 to 9 in a supercapacitor.